Public Financing in Education and Economic Growth of Nepal - Dangal, Dil Nath; Gajurel, Ram Prasad (Journal of Development and Administrative Studies, 2019)
Education serves as the foundation of human capital, enhancing productivity and innovation, and ultimately driving economic growth. This study aims to assess the relationship between public financing in education and Nepal's economic growth. Utilizing the ARDL error correction model with data spanning from 1982 to 2018, the findings indicate that public funding for education in Nepal negatively impacts long-term economic growth. In the short term, the enrollment of technical students at various institutions under Tribhuvan University also exhibits a negative association with Nepal's economic growth. The short-term setbacks may be attributed to the drain of technical expertise or insufficient investment in technical education, potentially impeding economic growth. Consequently, policymakers and stakeholders should prioritize technical education and domestic employability to foster sustainable economic growth in Nepal.